Ethnoecology-Based Traditional Agricultural Systems as a Strategy for Sustainable Agricultural Development - Kamakaula, Yohanes; Tjolli, Ihwan (PT. Hafasy Dwi Nawasena, 2026)
Sustainable agricultural development has become increasingly urgent due to environmental degradation, climate change, and rural socio-economic inequality caused by high-input modern agricultural systems. In this context, ethnoecology-based traditional agricultural systems offer an alternative framework grounded in local ecological knowledge, cultural values, and community-based resource governance. This study aims to analyze how traditional agricultural systems can be formulated as a strategic approach to sustainable agricultural development within modern policy frameworks. The research employed a qualitative design using in-depth interviews, participatory observation, and document analysis in rural communities practicing traditional agriculture. Data were analyzed through thematic coding and an interactive model of data reduction, display, and interpretation. The findings reveal three main dimensions: ecological sustainability through diversification and agroforestry practices; socio-institutional resilience through customary governance; and potential hybridization with modern technologies such as precision irrigation and climate-smart tools. The study concludes that integrating traditional ecological knowledge with contemporary agricultural innovation and legal recognition of customary institutions can strengthen inclusive and resilient sustainable agricultural development.